Analisis Bentuk Pembinaan Narapidana Di Lembaga Pemasyarakatan Kelas IIA Kalianda - Candra Dian Tawawi; Padmono Wibowo (Wajah Hukum, 2020)
Guidance is the state's effort for inmates to realize mistakes, not repeat, be accepted back, be active in the development, and live to be good and responsible citizens, under the function of guidance in prisons in the context of prisons, namely social reintegration. The research method used in the research is through a qualitative research approach where primary and secondary data are analyzed in the form of descriptions based on symptoms, and theory of association with additional/secondary data, the results are guidelines in the Class IIA Prison Kalianda Penitentiary obtained through personality development and independence activities. The stages of development for prisoners consist of initial, advanced, and final stages, the implementation of guidance by determining appropriate guidance for the correctional team session which is determined by the head of the correctional facility. Institutions coordinate with the security section, the constraints for coaching come from within prisoners who are less interested in participating in existing coaching programs or lack of coaching facilities and can be overcome through data collection, approaches, invitations to prisoners and collaboration with third parties as well as coaching results in the form of increased soft skills and can more devoted to God